Bilateral reversed palmaris longus muscle with trifid insertion, a rare variation - Gune, Anita R.; Pote, Anand J.; Patil, Ashalata D.; Patil, Priya S.; Nikam, Vasudha R. (International Journal of Research in Medical Sciences, 2017)
Normally the palmaris longus muscle originates from the medial epicondyle of the humerus from common flexor origin. In the middle of the forearm, the muscle belly forms a tendon which is inserted into the flexor retinaculum and the palmar aponeurosis. In our study after dissection of both forearms of a 45-year-old male cadaver we found a reversed palmaris longus muscle. This means that the palmaris longus muscle was tendinous in its proximal part and muscular in its distal part. The fleshy belly of muscle was passing over flexor retinaculum, was ensheathed by separate fascia. The muscle belly was spreading on both the sides of each palm for insertion which was trifid, that is centrally into palmar aponeurosis, laterally continuous with the fascia covering the thenar muscles and medially with Abductor digit minimi. It was having tendinous interconnection with the muscle mass of both the sides. Bilateral reversed palmaris longus muscle mentioned in the literature, was a surgical finding in a patient who suffered from edema and pain in the wrist. The overuse of the reversed palmaris longus muscle can lead to the muscle’s local hypertrophy. As per the literature a reversed palmaris longus muscle may cause a compartment syndrome with pain and edema in the wrist area, the carpal tunnel syndrome and Guyon’s syndrome. The variation is also useful to the hand surgeon, as the palmaris longus muscle is an anatomical landmark for operations in this area.